(3GdYQGFSs - (3CHh SYjO MHjH Gddg, cGf MjG ChGFd GdbQf (B11 (3g`s
(3ChdgG (B:s
.. (3de jhLO dCf hLhO GdTjAdG jbJVj YOe faSg hdG YOe TjA ef ceGdGJg hdh GbJVi GdTjA hYOe HYV eGdg ef GdceGdGJ dcGf ef GdTQ (B..s
(3BNQgG (B:s
... (3hCeG GdHGMK ajg Yf CMhGd GdeNJUI HGdeecfI Ch Yf CMhGd GdeNJUI HGdhGLH aGdChd jSei HGdCehQ GdYGeI hGdKGfj HGdLhGgQ hGdCYQGV (B...s
(3JHUQI GdYfhGf (B:s
(3aj Yde GdcdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B15 ( 1568)s
(3GdPQjYI (B15 - 175 ( 1568)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs